Effects of muscular injuries on the technical and physical performance of professional soccer players - Portillo, J.; Abián, P.; Calvo, B.; Paredes, V.; Abián-Vicén, J. (The Physician and Sportsmedicine, 2020)
Introduction: The aim of this study was to determine the effects of muscular injuries in the lower limbs on the technical and physical performance of professional soccer players when they return to the league competition.